A Fluorescent Hydrogen Peroxide Probe Based on a ‘Click’ Modified Coumarin Fluorophore - Du, Lupei (2010)
Herein a water-soluble ‘click’ modified coumarin-based fluorescent probe for hydrogen peroxide is reported. This probe shows significant intensity increases (up to 5 fold) in near-green fluorescence upon reaction with hydrogen peroxide, and good selectivity over other reactive oxygen species.